Um estudo sobre o ensino dos temas “Origem da Vida” e “Evolução Biológica” em dissertações e teses brasileiras (2006 a 2016) - Zabotti, Kamilla (2018)
The integrated understanding of the natural phenomena and biological process occurs thought the evolutionary thought, thus the Biological Evolution is considered the integrating and unifying base of Biological Science. Though the teaching of how life originated and diversified are the object of researches already developed and published in the last decades, some difficulties still remain in teaching these subjects. Taking these considerations into account, the present research is characterized as State of Art and it aims to highlight what is being produced in academic researches, in the form of dissertations and theses, from 2006 to 2016, regarding the teaching of the themes Origin of Life and Biological Evolution. A total of 78 articles were found, being 65 (83%) dissertations and 16 (17%) theses. 86% of these are from Higher Education Institutions (HEIs) of public administrative nature, with emphasis on state and federal universities, and 13% of private HEIs. Around 80% of dissertations and thesis are concentrated in the South-Southeast region. Half of the papers are dissertations on teaching Biological Evolution, and only one thesis investigates the teaching of the Origin of Life. Around 70% of the academic productions identified are intended for research at the secondary level on basic education. The continuing formation of teachers contemplates only 4% of the productions. In relation to the most prevalent issues in the set of dissertations and theses, stand out: Characteristic of Teacher, with 25%, followed by Didactic Resources and Method-Contents with almost 16% each, and History and Philosophy of Science, with 14%. We found three issues that were not well investigated in the researches: Curriculum and Programs, Non-Formal Education and School Organization, which appears as a research field little explored and that requires an investigation on the teaching and learning process of the Origin and Evolution of Life. These results, as well as the researches focused on the analysis of academic production, can contribute to the deployment of more specific proposals of teaching formation and improvements in the teaching-learning of the Origin of Life and Biological Evolution.